Validation of the Chilean Version of the Yale Food Addiction Scale 2.0 in Clinical and Non-Clinical Samples - Ximena Díaz-Torrente; Carina Valenzuela; Ana Palacio; Catalina Cuello; Alvaro Vergés; Marcela Reyes (Proceedings)
There is growing scientific evidence regarding the biological, psychological, and behavioral parallels involved in addiction and excessive food consumption. The Yale Food Addiction Scale 2.0 (YFAS2.0) is currently the only validated measure to operationalize addictive eating behavior. This scale has not been validated in the Chilean population; therefore, the aim of this study was to evaluate the psychometric properties of the culturally adapted version of YFAS2.0 for the Chilean population. An observational, analytical, and cross-sectional study was carried out. Sampling was non-probabilistic, by convenience. N = 466 participants were recruited, of which n = 160 formed the clinical sample (two clinical centers that specialized in the management of chronic non-communicable diseases), and n = 306 formed the non-clinical sample (universities and private companies). The adapted Chilean version of YFAS2.0 was applied using the online REDCap platform, then anthropometric measurements were made, and the body mass index (BMI) was calculated. The internal consistency of the YFAS2.0 items was estimated (Kuder–Richardson formula 20), and the structure of the scale was confirmed using a confirmatory factorial analysis. The association between the number of addictive symptoms and BMI was also evaluated. The sample was composed mainly of women (62.7%), with an average age of 35.7 ± 15.8 years. The prevalence of food addiction was 13.1% and 10.1%, and the number of addiction symptoms presented was 2.3 ± 2.6 and 2.1 ± 2.8 in the clinical and non-clinical samples, respectively. The Chilean version of YFAS2.0 presented good internal consistency (KR20 = 0.85), and the factor analysis supports the one-factor structure, similar to the original version, showing adequate fit indexes (CFI was 0.969; RMSEA was 0.063) with all the factor loadings greater than 0.57 Additionally, a slight positive correlation was observed between number of symptoms and BMI (rho = 0.23, p = 0.012). The adapted Chilean version of YFAS2.0 was validated in clinical and non-clinical samples, presenting good psychometric properties, so it can be considered for research studies on food addiction in the Chilean population.